A Sino-US Strategic Competition in the Indian Ocean Region: A Critical Analysis - Majeed, Dr. Gulshan; Khan, Muhammad Riaz; Butt, Amber (Journal of Nautical Eye and Strategic Studies, 2025)
This article critically examines the intensifying strategic rivalry between the United States and China in the Indian Ocean Region (IOR). Anchored in Realist Security Theory, the study explores the geopolitical, military, and economic dimensions of Sino-US competition, focusing on strategic interests, military posturing, maritime security, and infrastructure-based economic engagements such as the Belt and Road Initiative (BRI) and the U.S.-led Indo-Pacific Strategy. Employing a qualitative methodology enriched by case studies of key regional nodes Gwadar Port, Djibouti, and Diego Garcia the research evaluates the impact of great power rivalry on regional stability and state autonomy. The paper also reviews policy responses by regional actors and outlines future scenarios, offering policy recommendations for mitigating conflict while maintaining regional balance and sovereignty.